PENGARUH PROFITABILITAS, LEVERAGE, SIZE, KOMISARIS INDEPENDEN, DAN CURRENT RATIO TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Manufaktur Di Bursa Efek Indonesia BEI Pada Tahun 2012-2015) - Robertus Suganta Turnip, 13.05.52.0074; Kartika, Andi (Students Journal of Accounting and Banking, 2017)
This study aims to examine the effect of profitability, leverage, size, independent directors, and the current ratio against tax evasion on the financial statements of companies listed on the Stock Exchange Indonesia during the observation period. This research was done taking the population of manufacturing companies listed in Indonesia Stock Exchange in 2012-2015, using purposive sampling method. The sample in this study obtained 228 company in accordance with a predetermined kriterian. Data analysis technique used is multiple linear analysis menggnakan SPSS program.Â The results showed that no significant effect on the profitability of tax avoidance, leverage significant positive effect on tax avoidance, size is no significant effect on tax avoidance, the independent Commissioner significant positive effect on tax avoidance, and the current ratio significant positive effect on tax avoidance. This study uses agency theory.Keywords: Profitability, Leverage, Size, Independent Commissioner, Current Ratio, Tax Avoidance